Moderation of Predictor Variables on the Effect of Implementation of Government Accounting Standards and Accounting Understanding on the Quality of Financial Reports - Jati, I Ketut; Kresnandra, Anak Agung Ngurah Agung (Fakultas Ekonomi dan Bisnis Universitas Udayana, 2025)
This study aims to analyze the moderating effects of accounting information systems (AIS) and internal control systems (ICS) on the relationship between SAP implementation and accounting knowledge with financial statement quality. The research was conducted at the Regional Government of Badung Regency, with the population consisting of all accounting and finance staff at the Central Office. The sample was selected using purposive sampling. Data were collected through a questionnaire that had been tested for validity, reliability, and classical assumptions, and then analyzed using moderated regression analysis. The results indicate that SAP implementation positively affects financial statement quality, as does accounting knowledge. AIS was found to moderate the effects of both SAP implementation and accounting knowledge on financial statement quality, while ICS did not show a moderating effect on either relationship. These findings highlight the importance of an effective accounting information system in improving financial statement quality, whereas the internal control system needs to be strengthened to support the effectiveness of SAP implementation and accounting knowledge in government accounting practice.